PENGARUH ONLINE CUSTOMER REVIEW DAN KUALITAS WEBSITE TERHADAP MINAT BELI PAKAIAN DI SHOPEE - Nurul Artika Putri T; Rahmat Madjid; Nasrul Nasrul; Yusuf Yusuf; Isalman Isalman (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
The purpose of this study was to determine the partial effect of online customer reviews on buying interest, the effect of website quality on buying interest, and to determine the simultaneous effect of online customer reviews and website quality on buying interest. The research uses a quantitative approach which is carried out on students of the Faculty of Economics and Business. The sample in this study amounted to 60 students who had shopped at Shopee. Data were collected by questionnaire and analyzed using multiple linear regression. The results of this study indicate that partially online customer reviews have a positive and significant effect on consumer buying interest. Website quality has a positive and significant effect on consumer buying interest. Simultaneously online customer reviews and website quality have a significant influence on buying interest. From the results of the tests conducted, it was found that online customer review is the most dominant variable influencing buying interest.